A Young Girl with Bilateral Wrist Joint Deformity (Journal of Medicine, 2012)
Madelung deformity is a rare autosomal disorder involving the epiphyseal plate of distal radial end and consequent deformity. It is primarily found in adolescent females. A teenage girl presented with progressive bilateral wrist joint deformity and bowing of distal end of forearm without significant functional impairment and systemic complaints. Clinical examination was suggestive of Madelung deformity that was confirmed by Radiological evaluation. The pattern of deformity and radiology is the key to identify the disease. DOI: http://dx.doi.org/10.3329/jom.v13i1.7548JOM 2012; 13(1): 88-91